2017
DOI: 10.1039/c6ra28545g
|View full text |Cite
|
Sign up to set email alerts
|

Bio ionic liquids and water mixtures: a structural study

Abstract: In this study we have explored, by means of ab initio molecular dynamics, a subset of three different water/cho+–phe− mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…11 Their unabated popularity is related to the fact that these compounds are usually less harmful to the environment and are more readily biodegradable than the ILs obtained from synthetic substrates. 12,13 Naturally occurring L-carnitine, choline, or betaine cations are used to synthesize the majority of the bio-ILs, 14,15 while derivatives of fatty acids and carboxylic acids, such as acetic or formic acid, are often utilized as the source of the anion. 10,16,17 Bio-ILs derived from amino acids or sugars have also recently been described in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11 Their unabated popularity is related to the fact that these compounds are usually less harmful to the environment and are more readily biodegradable than the ILs obtained from synthetic substrates. 12,13 Naturally occurring L-carnitine, choline, or betaine cations are used to synthesize the majority of the bio-ILs, 14,15 while derivatives of fatty acids and carboxylic acids, such as acetic or formic acid, are often utilized as the source of the anion. 10,16,17 Bio-ILs derived from amino acids or sugars have also recently been described in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As disccused previously, the controllable friction behavior enabled in a wide range of humidity is attributed to the plentiful hydrogen bond donors and acceptors found in [Cho][Pro]. More importantly, Gontrani and coworkers found that the types of hydrogen bonds in Choline‐based IL/water mixtures could be determined by the water content, based on their molecular simulation and experimental studies . As schematically shown in Figure b, the water molecules prefer to establish H‐bonds with the cations and anions in the case of lower water content.…”
Section: Resultsmentioning
confidence: 74%
“…More importantly, Gontrani and coworkers found that the types of hydrogen bonds in Choline-based IL/water mixtures could be determined by the water content, based on their molecular simulation and experimental studies. [56,57] As schematically shown in Figure 6b, the water molecules prefer to establish H-bonds with the cations and anions in the case of lower water content. With the water concentration increase, IL pair formation decreases and H-bonds between water and water form, as shown in Figure 6c.…”
Section: Resultsmentioning
confidence: 99%
“…Analogous approaches based on a combined experimental and MD study by Gontrani et al ( 2017 ) have elucidated, using different degrees of water dilution in the IL, the behavior of hydrogen bonding between opposite- and like-charge dimers and the intercalation structure of the final solutions. These findings agree with what was found by Shyama and Lakshmipathi ( 2020 ) where 8 [EMIM][AA] ILs were investigated by DFT calculations.…”
Section: Structure and Computational Studiesmentioning
confidence: 99%